Decomposition of soil organic matter by ectomycorrhizal fungi: Mechanisms and consequences for organic nitrogen uptake and soil carbon stabilization - Tunlid, Anders; Floudas, Dimitrios; Op De Beeck, Michiel; Wang, Tao; Persson, Per (Frontiers in Forests and Global Change, 2022)
A major fraction of nitrogen (N) in boreal forest soils is found in organic forms associated with soil organic matter (SOM) and mineral particles. The capacity of ectomycorrhizal (ECM) fungal symbionts to access this N is debated, considering that these fungi have lost many of the genes for decomposing organic matter that were present in their saprotrophic ancestors. To gain a molecular-level understanding of the N-mining processes in ECM fungi, we developed an experimental approach where the processes of decomposition were studied in parallel with the changes in the structure and properties of the organic matter. We showed that ECM fungi have significant capacities to assimilate organic N associated with SOM and mineral surfaces. The decomposition mechanisms differ between species, reflecting the lignocellulose decomposition mechanisms found in their saprotrophic ancestors. During N-mining, the ECM fungi processed the SOM to a material with increased adsorptive properties to iron oxide mineral particles. Two pathways contributed to these changes: Extracellular modifications of the SOM and secretion of mineral surface reactive metabolites. Some of these metabolites have iron(III)-reducing activities and can participate in extracellular Fenton reactions and redox reactions at iron oxide mineral surfaces. We conclude that the traditional framework for understanding organic N acquisition by ECM fungi from recalcitrant SOM must be extended to a framework that includes how those decomposition activities affect the stabilization and reactivity of mineral-associated SOM. The activity through these complex networks of reactions is decisive for the overall effect of ECM fungal decomposition on nutrients and C-cycling in forest ecosystems.